Uptake of enrofloxacin from seawater to the macroalgae Ulva and its use in IMTA systems - Rosa, João (2020)
Integrated multi-trophic aquaculture systems can minimize the environmental impacts of aquaculture, while delivering economical benefits. However, the use of extractive species such as seaweeds can accumulate pharmaceuticals commonly used in these systems. Therefore, this work evaluated the exposure of the seaweed Ulva to enrofloxacin (ENR), a vastly used antimicrobial in aquaculture, at two dosages (C1, 7.5 μg L−1 and C2, 15 μg L−1), and concentrations in water and in Ulva were measured through time. Traditional endpoints such as growth and mortality were assessed as ENR effects in the macroalgae. Enrofloxacin presented good stability in seawater, and degradation rates were influenced by the presence of seaweed at the lowest concentration tested. The seaweed was able to assimilate the antibiotic, reaching internal concentrations of 7.76 ± 1.11 ng g−1 WW after 30 min of exposure for C1, and 14.51 ± 1.22 ng g−1 WW, after 15 min for C2. Lowest concentrations detected at the end of experimental time were 4.08 ± 0.42 ng g−1 WW and 5.09 ± 1.57 ng g−1 WW for C1 and C2, respectively, which nonetheless, corresponds to ∼5% of the maximum residue limit established for fish for ENR by the European regulation. The presence of ENR stimulated Ulva growth, with differences observed 96 h after the beginning of the trial.